2004
DOI: 10.1038/sj.bjc.6601512
|View full text |Cite
|
Sign up to set email alerts
|

A nested case–control study of stomach cancer in relation to green tea consumption in Japan

Abstract: To evaluate whether green tea consumption provides protection against stomach cancer, the relative risks (RRs) were calculated in the Japan Collaborative Study for Evaluation of Cancer Risk, sponsored by the Ministry of Health and Welfare (JACC Study). The study was based on 157 incident cases and 285 controls aged 40 -79 years. Cox proportional hazards regression analysis was used to estimate the RRs for stomach cancer. It was found that green tea consumption had no protective effect against stomach cancer. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 19 publications
0
32
0
Order By: Relevance
“…15) There are some epidemiological reports that the consumption of green tea infusion reduced the risk of gastric cancer in case-control studies. [16][17][18][19][20][21] In contrast, some researchers reported that the consumption of green tea was not associated with the reduction of gastric cancer using recent prospective studies. [22][23][24][25] In these reports that described the inhibitory effects or non-effects of green tea against cancer death, the relationship between the numbers of cups of green tea consumed and cancer death was examined, but the concentrations of catechins in the brewed tea infusion were not determined.…”
Section: Effect Of Green Tea On the Formation Of Nitrosamines And Camentioning
confidence: 99%
“…15) There are some epidemiological reports that the consumption of green tea infusion reduced the risk of gastric cancer in case-control studies. [16][17][18][19][20][21] In contrast, some researchers reported that the consumption of green tea was not associated with the reduction of gastric cancer using recent prospective studies. [22][23][24][25] In these reports that described the inhibitory effects or non-effects of green tea against cancer death, the relationship between the numbers of cups of green tea consumed and cancer death was examined, but the concentrations of catechins in the brewed tea infusion were not determined.…”
Section: Effect Of Green Tea On the Formation Of Nitrosamines And Camentioning
confidence: 99%
“…The other JACC Study 15 is the first study to analyze the effects of the consumption of green tea while controlling Helicobacter.pylori infection. After adjustment for age, smoking status, H. pyroli infection, history of peptic ulcer, family history of stomach cancer along with certain dietary elements, the risks associated with drinking one or two, three or four, five to nine, and 10 or more cups of green tea per day, relative to those of drinking less than one cup per day, were 1.1 (95% CI: 0.5-2.5), 0.9 (95% CI: 0.5-1.89), 0.8 (95% CI: 0.4-1.6), and 1.1 (95% CI: 0.5-2.3), respectively (p for trend=0.846).…”
mentioning
confidence: 99%
“…A nested case-control study was conducted in the JACC Study to evaluate the relationships between serum markers and risk of stomach cancer, and serum pepsinogen and H. pylori antibody was measured using sera from 164 death and 161 incidence cases of stomach cancer and 635 control subjects. 10,11 The current study was conducted to know what was the H. pylori and serum pepsinogen status, what factors were related to status of the serum markers among the control subjects, and what was the effect of them on the case-control study.…”
mentioning
confidence: 99%